Lumbar spine surgery across 15 years: trends, complications and reoperations in a longitudinal observational study from Norway - John-Anker Zwart; Jon Helgeland; Milada Cvancarova Småstuen; Kjersti Storheim; Margreth Grotle; Olaf Fjeld; Lars Grøvle; Tore K Solberg (BMJ Open)
Background Studies from different Western countries have reported a rapid increase in spinal surgery rates, an increase that exceeds by far the growing incidence rates of spinal disorders in the general population. There are few studies covering all lumbar spine surgery and no previous studies from Norway.Objectives The purpose of this study was to investigate trends in all lumbar spine surgery in Norway over 15 years, including length of hospital stay, and rates of complications and reoperations.Design A longitudinal observational study over 15 years using hospital patient administrative data and sociodemographic data from the National Registry in Norway.Setting and participants Patients aged ≥18 years discharged from Norwegian public hospitals between 1999 and 2013.Outcome measures Annual rates of simple (microsurgical discectomy, decompression) and complex surgical procedures (fusion, disc prosthesis) in the lumbar spine.Results The rate of lumbar spine surgery increased by 54%, from 78 (95% CI (75 to 80)) to 120 (107 to 113) per 100 000, from 1999 to 2013. More men had simple surgery whereas more women had complex surgery. Among elderly people over 75 years, lumbar surgery increased by a factor of five during the 15-year period. The rates of complications were low, but increased from 0.7% in 1999 to 2.4% in 2013.Conclusions There was a substantial increase in lumbar spine surgery in Norway from 1999 to 2013, similar to trends in other Western world countries. The rise in lumbar surgery among elderly people represents a significant workload and challenge for health services, given our aging population.